angiosperm radiation revisited, an ecological explanation for Darwin's 'abominable mystery' - Berendse, Frank; Scheffer, Marten (Ecology letters, 2009)
One of the greatest terrestrial radiations is the diversification of the flowering plants (Angiospermae) in the Cretaceous period. Early angiosperms appear to have been limited to disturbed, aquatic or extremely dry sites, suggesting that they were suppressed in most other places by the gymnosperms that still dominated the plant world. However, fossil evidence suggests that by the end of the Cretaceous the angiosperms had spectacularly taken over the dominant position from the gymnosperms around the globe. Here, we suggest an ecological explanation for their escape from their subordinate position relative to gymnosperms and ferns. We propose that angiosperms due to their higher growth rates profit more rapidly from increased nutrient supply than gymnosperms, whereas at the same time angiosperms promote soil nutrient release by producing litter that is more easily decomposed. This positive feedback may have resulted in a runaway process once angiosperms had reached a certain abundance. Evidence for the possibility of such a critical transition to angiosperm dominance comes from recent work on large scale vegetation shifts, linking long-term field observations, large scale experiments and the use of simulation models.